Human Resource Management for Early Childhood Education - Siti Zaenab (TARBIYA: Journal of Education in Muslim Society, 2016)
Abstract This study is aimed to describe the human resources in early childhood education which become basic needs for early childhood institutions that is in line with the vision to reach Indonesia Gold 2045. The focus of this research, can be divided into several sub-focuses; including the planning of recruitment, selection, assignment, development, and evaluation. The method used is phenomenological qualitative research with multi-case studies. The validity was done through applying credibility, dependibility, and confirmability. Data analysis technique conducted in each of the three cases using two approaches, namely (1) the analysis of individual cases and (b) cross-case analysis. The results of this study can be presented as follows: (a) human resources in early childhood education needs to be developed, so the goals can be successfully obtained. (b) The principal, teachers, and stakeholders need to be more progressive at the time of selection of qualified early childhood teachers S1, (c) to produce teachers and administrative staffs who have educational qualifications for early childhood education. The educational criteria required is S1 PG PAUD. Abstrak Penelitian ini bertujuan untuk menggambarkan mengenai sumber daya manusia pada pendidikan anak usia dini yang menjadi kebutuhan dasar bagi lembaga pendidikan usia dini yang sejalan dengan visi untuk mencapai Indonesia Gold 2045. Fokus penelitian ini dapat dibagi ke dalam beberapa subfokus; meliputi perencanaan penerimaan, pemilihan, penugasan, pengembangan, dan evaluasi. Merode yang digunakan adalah penelitian kualitatif fenomenologi dengan studi multikasus. Validitas dilakukan dengan menerapkan kredibilitas, reliabilitas, dan konfirmabilitas. Teknik analisis data dilakuakn pada setiap tiga kasus menggunakan dua pendekatan, yakni (1)Analisis kasus individu dan (2)analisis lintas kasus. Hasil Penelitian ini disajikan sebagai berikut: (a) sumber daya manusia pada pendidikan usia dini perlu dikembangkan, sehingga tujuan dapat sukses dicapai. (b) Kepala sekolah, para guru, dan pemangku kepentingan perlu lebih progresif saat memilih guru sekolah usia dini yang berkualifikasi S1 (c) untuk menghasilkan guru dan pegawai administrasi yang berkualifikasi pendidikan usia dini. Kriteria pendidikan yang dibutuhkan adalah S1 PG PAUD. How to Cite : Zaenab, S. (2016). Human Resource Management for Early Childhood Education. TARBIYA: Journal of Education in Muslim Society, 3(2), 242-251. doi:10.15408/tjems.v3i2.4063. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i2.4063